Nature & structure: merging blue & green landscape for holistic well being at Metropolitan Batu Park - Mohd Bohori, Nur Ayuni; Abu Bakar, Aniza; Ibrahim, Putri Haryati (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2019)
This project is about enhancing the holistic well-being of the community around Metropolitan Batu Park and Sungai Batu Retention Pond that might have face the urban issues in term of environment, social and economy aspect. Therefore this project is proposed to create an integration of the blue and green landscape element, infrastructure and technology in merging these two area into one family park that can give the platform in spreading the positive well-being effect to the users. The project is located at Metropolitan Batu Park which is 33 acres and Sungai Batu Retention Pond which is 253 acres. The total area is 286 acres. Figure 1 shows the key and location plan of the selected site. Both area is classified as zone A (Sungai Batu Retention Pond) that consist of natural retention pond area that is not accessible to public engagement, and Zone B (Metropolitan Batu Park) which is a lake park consist of few recreational activities however is not being fully utilized due to maintenance problem Both water bodies of these two area is from the ex-mining open pit that have turned into beautiful lakes. Figure 2 shows the zoning area between these two parks throughout the planning process and the demographic data of the community area. This two zone is separated by Jalan 1/18D, a newly constructed road crossing the area connected to the main road.